Downscaling hermit crab-gastropod network to demographic groups unveils recurrent patterns. Issue 1 (2nd January 2023) - da Silva, Alexandre R.; Rodrigues, Gabriel F.B.; Paluski, Geovana Bastos; Vieira, Neida Rodrigues; Gregati, Rafael A.
Abstract : We studied the hermit crab–shell interaction network of rocky shores in South Brazil using both community and populational (demographic groups) approaches which evaluated both inter and intraspecific perspectives. The community was composed of six hermit crab species and 33 gastropod shell species. We found a recurrent pattern in which the network structure was characterized by a modular and specialized pattern. The specialization at the species level varies in the community species and for ontogenetic groups. The configuration of the modules changed when switching from community to populational approaches, consisting of three and four modules, respectively. Resource partitioning must be a very important feature in these systems due to both the specific and demographic needs of each group. Our results reveal a pattern in which these types of interactions are modular and specialized, with those patterns being uncommon for non-mutualistic interactions in hermit crab-gastropod networks. The analyses showed difference in the network metrics when considering intra and interspecific perspectives. The mandatory nature of these interactions and the resource dynamics of the gastropod shells when occupied by hermit crabs may partially explain the patterns found for these unique interactions.